Effect of Work Life Balance on Job Satisfaction in Nepalese Commercial Banks - Ghimire, Shiva Raj; Agarwal, Nirdosh Kumar (Journal of Nepal Commerce Association, 2025)
This study examines the impact of work–life balance on job satisfaction among employees of Nepalese commercial banks. It focuses on key dimensions of work–life balance, including workplace support, work-to-family interference, family-to-work interference, and working hours, and evaluates their influence on employee satisfaction. The research adopts a descriptive and causal-comparative design, using primary data collected from 288 employees across 10 commercial banks in Nepal through convenience sampling. Correlation and regression analyses were employed to analyze the relationships between work–life balance factors and job satisfaction. The findings reveal that workplace support has a significant and positive effect on job satisfaction, while work-to-family interference, family-to-work interference, and long working hours exhibit strong negative relationships with employee satisfaction. Regression results further confirm that workplace support enhances job satisfaction, whereas interference between work and family roles and extended working hours reduce it. The study contributes to understanding work–life balance dynamics in Nepalese banks and highlights the importance of effective work–life balance policies for improving employee well-being and organizational performance.